Homophily in higher education research: A perspective based on co-authorships - Horta, H. (2022)
Research collaborations are the norm in science today, and are usually evaluated using co-authorships as the unit of analysis. Research collaborations have been typically analyzed using a mapping perspective that focuses on countries, institutions, or individuals, or by assessments of the determinants of research collaboration, i.e., who engages in collaborations and who collaborates the most. One analytical perspective that has been used less frequently is the homophily perspective, which attempts to understand the likelihood of research collaborations based on the similarity of collaborators’ preferences and attributes. In addition, compared to studies focused on the fields of the natural and exact sciences, engineering, and the health sciences, research collaborations in the social sciences have been underexamined in the literature, despite the growing numbers of social scientists who engage in such collaborations. This study assessed homophily with respect to geographical, ascribed, acquired and career-related attributes in co-authorships in the social sciences, based on a co-authorship matrix of 913 higher education researchers. The findings showed that geographic and institutional attributes were by far the most powerful homophilic drivers of collaborations, suggesting the importance of physical proximity, national incentives, and shared culture, language, and identity. Another driver was the similarity of acquired attributes, particularly certain preferences regarding research agendas; these absorbed the residual explanatory power that ascribed attributes such as gender or age had in co-authorship preferences. The study is novel in its analysis of the extent to which similarities in the research agendas of researchers predicted co-authorship. The findings indicate the need for further co-authorship homophily analyses around a broader set of acquired attributes and the trajectories that lead to them.